POLA ASUH ORANG TUA DENGAN PERKEMBANGAN BAHASA ANAK PRASEKOLAH (USIA 3-6 TAHUN) - Mulqiah, Zuraida; Santi, Eka; Lestari, Dhian Ririn (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Parenting style is a description used by parents for child care. Parenting style is one of thefactors that affect language development in children. The study was aimed to identify thecorrelation between parenting style and language development of pre-school children. The studyused cross sectional approach, total sampling. 40 mothers (90.9%) using democratic parentingstyle, 4 mothers (22,7%) authoritarian parenting style. The development of children's language isfound 34 children’s (77.3%) appropriate, 10 children’s (22.7%) with the result ofdoubtful. Showa correlation between parenting style and language development of pre-school children (age of 3-6 years old) (p= 0,032). The parenting style is one of the factors that influence the languagedevelopment of children; it is because the communication and interaction between children andparents have an important role so that children have language skills in accordance with thestages of the children's age.